The Genome Assembly and Annotation of the Southern Elephant Seal Mirounga leonina - Kim, Bo-Mi (Genes (Basel), 2020)
The southern elephant seal Mirounga leonina is the largest phocid seal and one of the two species of elephant seals. They are listed as ‘least concern’ by the International Union for Conservation of Nature (IUCN) Red List of Threatened Species 2015. Here, we have assembled the reference genome for M. leonina using the 10× chromium sequencing platform. The final genome assembly of M. leonina was 2.42 Gb long, with a contig N50 length of 54 Mb and a maximum length of 111.6 Mb. The M. leonina genome contained 20,457 predicted protein-coding genes and possessed 41.51% repeated sequences. The completeness of the M. leonina genome was evaluated using benchmarking universal single-copy orthologous genes (BUSCOs): the assembly was highly complete, containing 95.6% of the core set of mammalian genes. The high-quality genomic information on M. leonina will be essential for further understanding of adaptive metabolism upon repeated breath-hold dives and the exploration of molecular mechanisms contributing to its unique biochemical and physiological characteristics. The southern elephant seal genome project was deposited at NCBI (National Center for Biotechnology Information) under BioProject number PRJNA587380.